Pengaruh Komunikasi dan Kemampuan Kerja terhadap Kinerja Pegawai - Fitria Fitria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Organizational Performance is as a whole organizational effectiveness to meet the determined needs of each group that is related to systemic efforts and to increase the organization's ability to continuously achieve their needs effectively. This research was conducted to determine the Effect of Communication and Work Ability on Employee Performance at the Office of Food Crops, Plantations and Forestry, Lubuklinggau City. In this study used a three item variable questionnaire method, namely communication questionnaire (X1), work ability (X2) and employee performance variable (Y). The population and samples used in this study were 73 official employees of food crops, plantations and forestry in the city of Lubuklinggau. The data analysis technique used is the Analysis of Multiple Linear Regression. The results showed that there was a significant effect between communication and work ability on employee performance at the Lubuklinggau City Food, Plantation and Forestry Service Office. Furthermore communication (X1), and work ability (X2) contributes an influence of 64.9% on employee performance (Y). While the remaining 35.1% is influenced by other variables. Keywords: Communication, Work Ability and Performance